Efficacy and safety of once-daily, single-inhaler fluticasone furoate/umeclidinium/vilanterol versus fluticasone furoate/vilanterol in Japanese patients with inadequately controlled asthma: the CAPTAIN study. (2nd September 2021) - Nakamura, Yoichi; Hozawa, Soichiro; Sagara, Hironori; Ohbayashi, Hiroyuki; Lee, Laurie A.; Crawford, Jodie; Tamaoki, Jun; Nishi, Takanobu; Fowler, Andrew
Abstract: Objective: In CAPTAIN, a double-blind, parallel-group, Phase IIIA study, fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) improved lung function, symptoms and asthma control versus FF/VI in patients with inadequately controlled asthma. Here, we report efficacy and safety from a Japanese cohort in CAPTAIN. Methods: Adults with inadequately controlled asthma despite inhaled corticosteroid/long-acting β2 -agonist (ICS/LABA) were randomized (1:1:1:1:1:1) to once-daily FF/VI (100/25 mcg or 200/25 mcg) or FF/UMEC/VI (100/31.25/25 mcg, 100/62.5/25 mcg, 200/31.25/25 mcg, or 200/62.5/25 mcg) for ≥24 weeks. Endpoints included change from baseline in clinic trough FEV1 (primary), annualized rate of moderate/severe asthma exacerbations (key secondary), clinic FEV1 3 h post-dose, and Asthma Control Questionnaire (ACQ)-7, St George's Respiratory Questionnaire (SGRQ) (all Week 24), Evaluating Respiratory Symptoms (E-RS): Asthma total scores (Weeks 21–24) (all secondary). Adverse events and adverse events of special interest were monitored. Clinical trials.gov registry no: NCT02924688. Results: Overall, 229 of 2436 patients in the intention-to-treat (ITT) population were from Japan. In this cohort, change from baseline in trough FEV1 for FF/UMEC/VI 100/62.5/25 mcg versus FF/VI 100/25 mcg was 105 mL (95% confidence interval −5, 216) and 69 mL (–42, 179) for 200/62.5/25 mcg versus 200/25 mcg. These observations were supported by clinic FEV1 at 3 h post-dose. Moderate/severe exacerbation incidence was low and similar across pooled treatment groups (FF/VI, FF/UMEC 31.25 mcg/VI, FF/UMEC 62.5 mcg/VI). All pooled groups demonstrated clinically important improvements from baseline in ACQ-7, SGRQ and E-RS: Asthma total scores. Safety profiles were consistent with the overall ITT population, with no new safety concerns. Conclusion: FF/UMEC/VI is an effective option with a favorable risk-benefit profile in Japanese patients with uncontrolled moderate or severe asthma on ICS/LABA.